P272 Managing suspected pulmonary embolism in an ambulatory setting: the Barking Havering and Redbridge University Hospitals experience. (12th November 2015) - Kleidona, F; Salehi, A; Dunne, C; Choudhury, A; Johns, RH
Abstract : Introduction and objectives: There is an increasing national precedent for ambulatory care of selected patients with suspected pulmonary embolism (PE). 1 As part of our ambulatory services we established an ambulatory PE pathway in January 2012 with the intention to reduce hospitalizations and cost without any associated risk. Methods: We conducted a retrospective review of all 165 patients referred to the ambulatory service for suspected PE between January 2012 and May 2013. We included 122 patients and we reviewed all medical notes, laboratory and radiological investigations. Results: In 5 patients (4%), PE was confirmed after imaging. The mean age was 50 years with 68.5% female patients. The most common presenting complaint was chest pain followed by dyspnoea. In 59% of cases the Well's score was not documented. D-Dimer was checked in 94.5% of patients with unnecessary measurement in 11% of these. In 20% of patients who had radiological investigations for PE, D-dimer was negative. ECG and CXR were performed in most of cases with abnormal findings in 11% and 15% respectively. 77% of patients underwent CTPA, 21% had a V/Q scan, and 2% had V/Q scan followed by CTPA. The mean time to scan was 1.5 days with minimum of 1 day and maximum of 4 days. All confirmed PEs were identified by CTPA and were provoked by risk factors such as recent surgery, recent pregnancy, oral contraceptives, previous documented VTE. Domiciliary enoxoparin was administered in 89% of patients pending CTPA or VQ. All confirmed PEs were subsequently treated with warfarin. No complications occurred, including bleeding events, recurrent VTEs, readmissions for anticoagulation related events, or deaths related to PE. Conclusions: Our experience shows that selected patients with suspected PE can be safely managed as outpatients in our trust. Closer adherence to the pathway may prevent a number of unnecessary scans (i.e. PE can be safely excluded when Wells score low and D-Dimer negative without a scan). Our protocol and pathways are being updated to incorporate PESI criteria to safely identify ambulatory patients, and to use of rivaroxoban in preference to warfarin for confirmed PE. Reference: 1 Ladwa RM, et al . Thorax 2011;66 :A160